Antiproliferative effect of plant sterols at colonic concentrations on Caco-2 cells. (December 2017) - López-García, Gabriel; Cilla, Antonio; Barberá, Reyes; Alegría, Amparo
Highlights: Individual plant sterols have cytostatic effect on Caco-2 cells. Combined plant sterols displayed greater antiproliferative effect. The intake of plant sterol-enriched beverages may help combat colon cancer. Abstract: Plant sterols (PS) have been incorporated to foods due to their cholesterol-lowering effect. Because of their low intestinal absorption (0.5–2%), they can reach the colon and exert local actions. The aim of this study was to evaluate the antiproliferative effect of individual (β-sitosterol, campesterol and stigmasterol) and combined PS in colon cancer cells (Caco-2) at human colonic concentrations after simulated gastrointestinal digestion of a PS enriched milk-based fruit beverage. β-Sitosterol, campesterol and stigmasterol induced significant cell viability reduction (13–59% vs control), but only stigmasterol produced an overproduction of reactive oxygen species (92% vs control). Individual PS induced reversible arrest in phase G0 /G1 of the cell cycle, suggesting that they act as cytostatic agents. Combined PS showed a greater effect than individual PS, inducing also cell necrosis and irreversible cell cycle arrest (G0 /G1 phase). The consumption of PS-enriched foods therefore could exert a potential preventive effect against colon cancer.